Analisis Unsur-Unsur yang Menentukan Tingkah Laku Kepemimpinan, Konsep Dasar Kepemimpinan, dan Syarat-Syarat Kompetensi Pemimpin Pendidikan Islam - Kartika, Ika; Abriansyah, Faisal; Abdul Aziz, Haris; Handayani, Dina; Aulia, Frida (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
This study aims to identify and analyze the elements that determine leadership behavior, basic concepts of leadership, and the requirements for leader competence in the context of Islamic education. Effective leadership in Islamic educational institutions has an important role in achieving strategic goals and building a conducive educational environment. The elements that determine leadership behavior include personal characteristics, leadership styles, and interacting environmental influences. This research also explores various basic concepts of leadership from traditional to modern perspectives, complemented by Islamic values such as justice, honesty, and example. In addition, the study identifies the competency requirements of Islamic education leaders, including academic ability, managerial skills, as well as moral and spiritual qualities needed to effectively manage educational institutions. Through a qualitative approach, this research collects data from various relevant literature and case studies. The results showed that successful leadership in Islamic education is not only based on managerial skills, but also on moral integrity and commitment to Islamic values. This research is expected to provide insight for academics, practitioners, and policy makers in developing leadership models that are effective and in accordance with Islamic principles, as well as support the improvement of the quality of education in Islamic educational institutions.